Cyclin A2 modulates kinetochore–microtubule attachment in meiosis II - Zhang, Qing-Hua; Yuen, Wai Shan; Adhikari, Deepak; Flegg, Jennifer A.; FitzHarris, Greg; Conti, Marco; Sicinski, Piotr; Nabti, Ibtissem; Marangos, Petros; Carroll, John (The Journal of cell biology, 2017)
Cyclin A2 is a crucial mitotic Cdk regulatory partner that coordinates entry into mitosis and is then destroyed in prometaphase within minutes of nuclear envelope breakdown. The role of cyclin A2 in female meiosis and its dynamics during the transition from meiosis I (MI) to meiosis II (MII) remain unclear. We found that cyclin A2 decreases in prometaphase I but recovers after the first meiotic division and persists, uniquely for metaphase, in MII-arrested oocytes. Conditional deletion of cyclin A2 from mouse oocytes has no discernible effect on MI but leads to disrupted MII spindles and increased merotelic attachments. On stimulation of exit from MII, there is a dramatic increase in lagging chromosomes and an inhibition of cytokinesis. These defects are associated with an increase in microtubule stability in MII spindles, suggesting that cyclin A2 mediates the fidelity of MII by maintaining microtubule dynamics during the rapid formation of the MII spindle.